Hirshfeld Surface Analysis and Crystal Structure of [2-Bromo-4-(4-Fluoro-Benzoyl)-Phenoxy]-Acetic Acid Ethyl Ester. (12th April 2016) - Rani, N. Latha; Prashanth, T.; Sridhar, M. A.; Ranganatha, V. Lakshmi; Shaukath, A. K.
ABSTRACT: The title compound C17 H14 BrFO4 was synthesized using 3-Bromo-4-hydroxy-phenyl-(4-fluoro-phenyl)-methanone, ethyl chloroacetate, and anhydrous potassium carbonate. Its structure was established using elemental analysis, NMR, and single crystal X-ray diffraction techniques. The compound crystallizes in orthorhombic crystal system and space group Pbca. The cell parameters are a = 10.1444(13) Å, b = 8.2781(10) Å, c = 38.423(5) Å, Z = 8, V = 3226.6(7) Å 3 . The dihedral angle between two least squares planes of two phenyl rings bridged by keto carbonyl group is −28.2(5)°. The molecule exhibits intermolecular interactions of the type C‒H…F and C‒H…O. The intercontacts in the crystal structure are studied using Hirshfeld surface analysis.